The Ferrojan Horse Hypothesis: Iron-Virus Interactions in the Ocean - Bonnain, Chelsea; Breitbart, Mya; Buck, Kristen N. (Frontiers in Marine Science, 2016)
Iron is an essential nutrient and the sub-nanomolar concentrations of iron in open ocean surface waters are often insufficient to support optimal biological activity. More than 99.9% of dissolved iron in these waters is bound to organic ligands, yet determining the identity of these ligands in seawater remains a major challenge. Among the potential dissolved organic ligands in the colloidal fraction captured between a 0.02 and a 0.2 μm filter persists an extremely abundant biological candidate: viruses, most of which are phages (viruses that infect bacteria). Recent work in non-marine model systems has revealed the presence of iron ions within the tails of diverse phages infecting Escherichia coli. Based on these findings and the presence of conserved protein motifs in marine phages, here we present several lines of evidence to support the hypothesis that phages are organic iron-binding ligands in the oceans. With average concentrations of 107 phages per milliliter surface seawater, we predict that phages could contain up to 0.7 pM iron, a value equivalent to as much as 70% of the colloidal fraction of organically complexed dissolved iron in the surface ocean. Additionally, the production and uptake of siderophores, a strategy that bacteria have developed for assimilating iron, renders cells vulnerable to phage infection due to the dual function of these cell surface receptors. Iron ions present in phage tails enable phages to exploit their bacterial host's iron-uptake mechanism via the “Ferrojan Horse Hypothesis” proposed herein, where the apparent gift of iron leads to cell lysis. Finally, if host iron stores are recycled during the assembly of progeny phages, as much as 14% of the cellular iron released into the water column upon lysis would already be incorporated into new phage tails. The potential role of phages as iron-binding ligands has significant implications for both oceanic trace metal biogeochemistry and marine phage-host interactions.